Global pentecostal and charismatic healing - Brown, Candy Gunther (Oxford University Press, 2011)
Divine healing is the essential marker of the global phenomenon of Pentecostal and charismatic Christianity. The essays in this collection seek to discover what is the same and what is different about such beliefs and practices in diverse contexts and much more.